Development of a high strength and high ductility near β-Ti alloy with twinning induced plasticity effect. (November 2018) - Ren, Lei; Xiao, Wenlong; Ma, Chaoli; Zheng, Ruixiao; Zhou, Lian
Abstract: A multi-alloyed near β-Ti alloy Ti-6Cr-4Mo-2Al-2Sn-1Zr (Ti-64221) with high strength and high ductility was designed utilizing the d -electron theory combined with molybdenum equivalence approaches. Mechanical properties and microstructural evolution of the β-solution treated alloy were investigated. The results show that Ti-64221 alloy exhibits excellent tensile strength, ultra-high total elongation and high ability of strain hardening. The product of strength and elongation is as high as 42.6 GPa% exceeded those achieved earlier in β-Ti alloys. Mechanical activation of 332〈113〉 and 112〈111〉 twinning and the stress-induced phase transformation during the process of plastic deformation are benefited for enhanced strength and ductility. Graphical abstract: Unlabelled Image